'A one-sided affair': unilateral pulmonary oedema and the role of cardiac MRI in diagnosing premature coronary artery disease in a patient with Prader-Willi syndrome. (22nd May 2013) - Jabbar, Avais; Khan, Jamal N; Singh, Anvesha; McCann, Gerry P
Abstract : There is no formal association between premature coronary artery disease (CAD) and Prader-Willi syndrome despite its association with hyperlipidaemia, diabetes mellitus and hypertension. A 36-year-old man with Prader-Willi syndrome presented with acute breathlessness. Inflammatory markers were borderline elevated and chest radiography demonstrated unilateral diffuse alveolar shadowing. Bronchopneumonia was diagnosed and despite treatment with multiple courses of antimicrobial therapy, there was minimal symptomatic and radiographical improvement. A diagnosis of unilateral pulmonary oedema was suspected. Echocardiography was non-diagnostic due to body habitus and coronary angiography was deemed inappropriate due to uncertainty in diagnosis, invasiveness and pre-existing chronic kidney disease. Therefore, cardiac magnetic resonance was performed, confirming severe triple-vessel CAD. This case demonstrates a presentation of heart failure with unilateral chest radiograph changes in a young patient with Prader-Willi syndrome and severe premature CAD detected by multiparametric cardiac magnetic resonance imaging.